Performance Evaluation and Mechanism Study of Seawater-Based Circulatory Fracturing Fluid Based on pH-Regulated WormLike Micelles - Tang, Haifeng; Song, Jiamei; Zhao, Min; Zhang, Zhiyang; Liu, Weixing; Yan, Zhihu (Frontiers in Chemistry, 2022)
In this article, a novel salt-resistant pH-sensitive surfactant N-carboxystearamido methanesulfonic acid (MSA) was designed and synthesized. The rheological properties of the MSA/CTAB mixed system prepared using seawater were evaluated, and the variation laws of the related rheological parameters were discussed. The relevant fracturing technical parameters of the MSA/CTAB mixed system were comprehensively evaluated. The wormlike micelles formed by the non-covalent binding of MSA and CTAB molecules can resist the electrostatic effect of inorganic salts in the seawater. Meanwhile, the MSA/CTAB mixed system has an excellent pH response and revealed that the change from wormlike micelles to spherical micelles leads to the decrease of the apparent viscosity and the transition from Maxwell fluid to Newton-type fluid. Furthermore, the MSA/CTAB mixed system has excellent cyclic fracturing performance, which can meet the dual requirements of fracturing fluid cost and performance of offshore oilfield, and has a good application prospect.